THE ANALYSIS OF INTELLECTUAL PROPERTY RIGHTS IN CHINA - Wibowo, Edwin Agung (Universitas Riau Kepulauan, 2014)
This paper has used a comparative study for the key findings of the experimental studies.Â The several aspects such as the legal framework, economic, culture and macro environment are subjected to be compared to measure the main gap as the issues between theoretical legal framework and IPR administrative procedures in China.Â In addition, this paper includes several sources of experimental data from library, journals and Internet in order to obtain the accurate information for the comparative study.